Hernando Cortes and the Conquest of Mexico. - De Angelis, Gina (Philidelphia : Chelsea House, 2000)
A biography of the explorer whose brutal conquest of the Aztecs was responsibile for the first Spanish settlements in the New World.
Keywords: Cortes,Hernan 1485-1547 Juvenile LIterature; Mexico-History-Conquest, 1519-1540 Juvenile Literature; Mexico-Discovery and Exploration-Spanish Juvenile Literature; Conquererors-Mexico Biography Juvenile Literature; Explorers-Mexico-Biography Juvenile Literature; Explorers-Spain-Biography Juvenile Literature